Apical Periodontitis Healing Following Treatment is Impacted by Root Canal Sealer Composition: An in Vivo and in Vitro Investigation - Léa Assed Bezerra da Silva; Kléber Cortês Bonifácio; Fernanda Souza Liévana; Giovana Gonçalves Martins; Daniel Silva-Herzog Flores; Mário Roberto Leonardo; Raquel Assed Bezerra da Silva; Francisco Wanderley Garcia Paula-Silva (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the periapical healing following root canal treatment in teeth with apical periodontitis (in vivo) and the cytotoxic potential of root canal sealers in vitro. Material and Methods: Apical periodontitis was induced in 60 dogs' teeth and root canals were filled with Sealapex (40 roots), EndoREZ (40 roots), intracanal dressing (20 roots), or left untreated (20 roots). After 30 and 90 days, histopathological analyses were made. In vitro, J774.1 macrophages were stimulated with root canal sealers extracts, cytotoxicity was assessed using lactate dehydrogenase assay, and qRT-PCR was used to analyze TNF-α gene expression. Results: In vivo, smaller apical periodontitis and lower inflammatory cell infiltrate were found in teeth treated with Sealapex compared to EndoREZ. In vitro, EndoREZ was cytotoxic and induced TNF-α gene expression by macrophages differently from Sealapex. Conclusion: Sealapex allowed improved tissue repair following root canal treatment in teeth with apical periodontitis compared to EndoREZ. Synthesis of TNF-α induced by LPS was enhanced by EndoREZ, whereas Sealapex prevented pro-inflammatory gene expression.